Performance of carbide cutting tools when machining of nickel based alloy - Noor M.M.; Kadirgama K.; Habeeb H.H.; Rahman M.M.; Mohammad B. (2023)
This paper was investigated the behavior of cutting tools when machining of nickel based alloys 242. Experiments were conducted using four different cutting tool materials under wet condition. Tool failure modes and wear mechanism were examined at various cutting parameters. Flank wear found to be the predominant tool wear for all cutting tools especially with CVD tools. Attrition lead to exposure and build up edge of the wear mechanisms were observed in all cutting tools. Coating is observed to be delaminated as main phenomena on cutting tools surfaces. The obtained results are PVD cutting tools perform better than CVD in terms of tool life with machining parameters. 2010 Springer-Verlag France.